O papel do juiz na direção do processo civil no estado democrático de direito : a direção material voltada à construção da solução jurídica do caso concreto - Rodrigues, Enrique Feldens (2013)
This paper examines the role of the judge in conducting civil cases throughout history since the Middle Ages, during which germinated the formation of the two legal traditions of the Western world - civil law and common law. It starts with the approach of the relationship between the political and social context to jurisdiction, seeking to establish the connection between the concentration and the strengthening of state power, the centralization of legal activity in the state and the appreciation of the task of legal rules enforcement by the courts, determined in civil law, on the one hand, and the devolution of political power, the overvaluation of the parties performance and the prominence of the particularities of the case, attested in common law, on the other, with the formatting process of two contrasted models, both aiming to solve the conflict, and, nevertheless, absorbing differently the partial change in the purpose of government action during the transition state from liberal to welfare state. It follows the finding that, despite the assignment of a positive responsibility to conduct the case to the judge since the late nineteenth century, each tradition reacted in its own way, demonstrating the obvious disadvantages of the bulking of judicial discretion in English and especially American settings and the assumption of an authoritarian-interventionist posture in Continental and Latin-American sceneries. Following the approach, it is portrayed the contours assumed by legal phenomenon in a democratic state under rule of law, in which, given the recognition of normative principles, legal process should become the arena where concrete cases are effectively debated and decided with reference to legal and constitutional system. As a result, it is recognized the need that such results obtain a procedural and substantive legitimacy, which is achieved by allowing parties to participate in the construction of the solution that involves their cause, but whose gear is driven by the judge, who has the duty to give hints and feedbacks as it is embodied in the German procedural system in order to attain the conformation of a suitable procedure, balanced and real opportunities of thorough discussion, a quick decision and a disposition by settlement, when appropriate.